2016
DOI: 10.1007/s40620-016-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dapagliflozin on renal function in patients with type 2 diabetes

Abstract: In patients with normal or mildly impaired renal function, dapagliflozin is not associated with increased risk of acute renal toxicity or deterioration of renal function. All trials included in this analysis are registered at ClinicalTrials.gov: NCT00263276, NCT00972244, NCT00528372, NCT00736879, NCT00528879, NCT00855166, NCT00357370, NCT00680745, NCT00683878, NCT00673231, NCT00643851, NCT00859898.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 32 publications
6
51
0
2
Order By: Relevance
“…However, this might result from a mixture of initial eGFR dipping and long-term eGFR preservation. We noticed a pattern of eGFR reduction in the short-term studies and eGFR preservation in the longer-term studies, as has been reported in several clinical trials (Cefalu et al, 2013; Kohan et al, 2014; Lambers Heerspink et al, 2013; Strojek et al, 2011; Wanner et al, 2016; Yale et al, 2013), including the EMPA-REG OUTCOME study (Wanner et al, 2016), and pooled analyses (Kohan et al, 2016; Yamout et al, 2014). This pattern, as well as the reversibility of eGFR after drug discontinuation (Barnett et al, 2014; Wanner et al, 2016), suggests that initial reduction of eGFR is probably caused by hemodynamic changes, either acute volume contraction or rapid upregulation of TGF, rather than by structural damage.…”
Section: Discussionsupporting
confidence: 79%
“…However, this might result from a mixture of initial eGFR dipping and long-term eGFR preservation. We noticed a pattern of eGFR reduction in the short-term studies and eGFR preservation in the longer-term studies, as has been reported in several clinical trials (Cefalu et al, 2013; Kohan et al, 2014; Lambers Heerspink et al, 2013; Strojek et al, 2011; Wanner et al, 2016; Yale et al, 2013), including the EMPA-REG OUTCOME study (Wanner et al, 2016), and pooled analyses (Kohan et al, 2016; Yamout et al, 2014). This pattern, as well as the reversibility of eGFR after drug discontinuation (Barnett et al, 2014; Wanner et al, 2016), suggests that initial reduction of eGFR is probably caused by hemodynamic changes, either acute volume contraction or rapid upregulation of TGF, rather than by structural damage.…”
Section: Discussionsupporting
confidence: 79%
“…A large pooled analysis of 12 randomized clinical trials of up to 24 (4,545 patients) or 102 (3,036 patients) weeks explored the effects of dapagliflozin on renal function in patients with type 2 diabetes with normal or mildly impaired renal function (48 (48). In addition to the effects on GFR, SGLT2 inhibitors also influence albuminuria.…”
Section: Sglt2 Inhibitors and Renal Function In Clinical Studiesmentioning
confidence: 99%
“…[59] Dapagliflozin, on the other hand, has been studied only in patients with normal or mildly impaired renal functioning but it has been associated with favorable effects on renal end points. [6061] In a retrospective meta-analysis, dapagliflozin has also demonstrated a reduction in proteinuria, suggestive of possible benefit for the proteinuria end point. Confirmatory evidence on the renal benefit of dapagliflozin is awaited from prospective trials.…”
Section: Sodium–glucose Co-transportersmentioning
confidence: 99%
“…Confirmatory evidence on the renal benefit of dapagliflozin is awaited from prospective trials. [6061]…”
Section: Sodium–glucose Co-transportersmentioning
confidence: 99%